PENGARUH KECERDASAN INTELEKTUAL PADA PEMAHAMAN AKUNTANSI DENGAN KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL SEBAGAI VARIABEL PEMODERASI - Pasek, Nyoman Suadnyana; Dwirandra, A. A. N. B.; Putri, I G. A. Made Asri Dwija (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 04.NO.10.TAHUN 2015, 2016)
This study aims to reveal the effect of the intellectual at the level of understanding of accounting, moderating by emotional intelligence and spiritual intelligence. The method used in this research is explanatory research, which would explain the causal relationship between the independent variable on the dependent variable that is reinforced by moderating variables through hypothesis testing. Data collected through questionnaires and secondary data. While the data analysis includes descriptive analysis, the classical assumption test and verification analysis using Moderated Regression Analysis (MRA). Based on the results of this research is that (1) The intellectual positive and significant impact on the understanding of accounting. This means that with good intelligence quotient, the student will be easier to understand about the understanding of accounting, (2) Emotional intelligence can enhance intellectual influence on the level of understanding of accounting is positive and significant. (3) Spiritual intelligence can enhance intellectual influence on the level of understanding of accounting is positive and significant. Therefore, someone who has a high spiritual intelligence will also motivate students to study harder and have higher creativity.
Keywords: Kecerdasan Intelektual; Kecerdasan Emosional; Kecerdasan Spiritual; Pemahaman Akuntansi